Isolation and characterisation of light harvesting complexes from bacteria of the genus Gemmatimonas - Dachev, Marko (Jihočeská univerzita, 2015)
Photosynthetic bacteria are highly abundant. The isolation and characterization of the light-harvesting complex from the Gemmatimonas phototrophica AP64T which belongs to the seventh phylum of the evolutionary important (bacterio)chlorophyll-containing bacteria are reported here. The purification of the complex was achieved by gel-filtration and electrophoresis. HPLC was used for identification of the pigments. The protein subunits were further identified by MS analysis.
Isolation and characterisation of light harvesting complexes from bacteria of the genus Gemmatimonas